Queer politics in India :towards sexual subaltern subjects - Shraddha Chatterjee (New York, 2018)
Queer Politics in India simultaneously tells two interconnected stories. The first explores the struggle against violence and marginalization by queer people in the Indian subcontinent, and places this movement towards equality and inclusion in relation to queer movements across the world. The second story, about a lesbian suicide in a small village in India, interrupts the first one, and together, these two stories push and pull the book to elucidate the failure and promise of queer politics, in India and the rest of the world.